Engineering Support in the Machine Manufacturing Domain through Interdisciplinary Product Lines: An Applicability Analysis. Issue 3 (2015) - Feldmann, Stefan; Legat, Christoph; Vogel-Heuser, Birgit
Abstract: The increasing challenge to manufacture individual products in short periods of time necessitates a huge amount of machine variants. Therefore, the efforts in engineering as well as in managing the variability increase. An adequate support in modelling such variant-rich systems enhances reuse of variable parts of the machine and, by that, promises an improvement of efficiency during development. To provide a first step into this direction, this paper analyses the applicability of an interdisciplinary product line approach as one means to improve the engineering in the machine manufacturing domain.